The chiral Hall effect in canted ferromagnets and antiferromagnets - Jonathan Kipp (Nature Portfolio, 2021)
The Hall effect is about the generation of a transverse voltage when a longitudinal current is applied and many mechanisms can lead to Hall effect in magnetic material. Here, the authors report a chiral Hall effect that is proportional to the vector spin chirality in canted magnetic materials.